PERAN BRAND IMAGE MEMEDIASI PENGARUH CELEBRITY ENDORSER TERHADAP REPURCHASE INTENTION - Febrianda Melzica, Ni Putu Dellya; Wardana, I Made (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.09.TAHUN.2022DO - 10.24843/EEB.2022.v11.i09.p06, 2022)
Celebrity endorsers are one of the factors that influence a person's intention to buy or reuse (repurchase intention) a product or service. The use of celebrity endorsers in promotions can increase repurchase intention. This study wants to explain the role of brand image in mediating celebrity endorsers on repurchase intention. This research was conducted in Denpasar City involving 80 respondents. The data collection method used is purposive sampling. Data was collected by distributing questionnaires containing statements related to celebrity endorser variables, brand image and repurchase intention. Furthermore, the data from the questionnaire collection was processed using validity and reliability tests to determine the feasibility and consistency of indicators in the questionnaire. In addition to validity and reliability tests, other tests were conducted, namely path analysis and Sobel test. The results showed that celebrity endorser had a positive and significant effect on repurchase intention. Meanwhile, brand image has a positive and significant effect on repurchase intention. So it can be said that to increase repurchase intention, it can be done by increasing the use of celebrity endorsers and growing a good brand image.